2021
DOI: 10.3390/molecules26133939
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Fibre Multigrain Bar Technology with the Addition of Curly Kale

Abstract: The aim of this study was to find the effect of kale and dietary fibre (DF) on the physicochemical properties, nutritional value and sensory quality of multigrain bars. A recipe of multigrain bars was prepared with the addition of fresh kale (20% and 30%) and DF preparations (apple, blackcurrant, chokeberry and hibiscus). The bars were baked at 180 °C for 20 min. These snack bars, based on pumpkin seeds, sunflower seeds, flaxseed and wholegrain oatmeal, are a high-calorie product (302–367 kcal/100 g). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In other words, the evaluators significantly preferred the darker bars. Further studies also revealed that a higher colour saturation is synonymous with consumers' perception of being "more alive" [67].…”
Section: Sensory Evaluationmentioning
confidence: 94%
“…In other words, the evaluators significantly preferred the darker bars. Further studies also revealed that a higher colour saturation is synonymous with consumers' perception of being "more alive" [67].…”
Section: Sensory Evaluationmentioning
confidence: 94%
“…The content of chlorophyll and carotenoid pigments in the sample were calculated in mg per 100 g dry matter (d.m.) from the following equations [44]: The total phenolic content was determined by spectrophotometric method with the use of the Folin-Ciocalteu reagent, which consisted of a colored reaction of phenolic compounds with this reagent [45]. To perform the test, 15% sodium carbonate (0.5 mL), distilled water (8.9 mL), acetone extract of the sample (0.5 mL; the extract was prepared in the same way as for the determination of carotenoids/chlorophylls), and 100 µL of Folin-Ciocalteu reagent were added to the tube.…”
Section: Carotenoids and Chlorophyll A And B Contentmentioning
confidence: 99%
“…The various multi-grains products that were developed with healthy approaches are noodles (Kudake et al, 2017(Kudake et al, , 2018Muley et al, 2015) and bread (Malik et al, 2016), nutria-bars (Kowalska et al,2021) and porridge mix (Hussain, 2018). Recently, Panghal et al 2018 emphasized the utilization of fruits, vegetables, and legumes in the formulation of a non-dairy probiotic drink which is packed with functional and nutritious components.…”
Section: Figure 2 Global Functional Food Market Sharesmentioning
confidence: 99%
“…Foods with health advantages referred to as functional foods have grown in popularity as a result of those who desire to use food as a natural medicine (Cencic & Chingwaru, 2010). Frequent consumption of wholesome grains improves healthy lifestyles because of the increased nutrient profile and high bioactive components present in whole grains (Kowalska et al, 2021). People, who live in the twenty-first century, are too busy and they have less time to cook grains since it is time-consuming.…”
Section: Introductionmentioning
confidence: 99%